Electrical Conductivity and Viscosity of Nigerian Traditional Soaps in Non-aqueous Solvents. - Adebajo, Moses Olorunfemi (Obafemi Awolowo University, 2014)
The electrical conductance and viscosities of different concentrations of alcoholic solutions of Nigerian traditional soap are measured as a function of temperature. Sodium, potassium and potassium/sodium (50:1) soaps are prepared from palm kernel oils using laboratory reagent alkalis. Their conductances are also measured. While the conductance values vary with the state of purity of the soaps and the polarity of the solvents, no significant change is observed in viscosity in relation to their purity.